Microbiological profile and antibiotic resistance pattern of urinary tract infection in a tertiary care hospital - R., Vismaya V.; Shajihan, Naiema; Ramesh, Midhun; Devi, Ambika (International Journal of Basic & Clinical Pharmacology, 2021)
Urinary tract infection (UTI), of varying severity is one of the most commonly encountered ailments in nephrology outpatient department (OPD). The commonest pathogens causing community acquired UTI (CAUTI) are E. Coli, Proteus mirabilis, Pseudomonas aeruginosa and Klebsiella pneumonia. There is a rapidly rising trend of antibiotic resistance among these uropathogens, may be due to indiscriminate antibiotic usage and poor patient compliance. We conducted a retrospective analysis of all culture proven UTI cases that attended the nephrology OPD of S. K. hospital, Trivandrum from August 2017 to July 2019 (24 months). 130 males and 121 females were included in the study. The mean age of the study group was 62.8 years with a male predominance in the age group above 50 years and a female predisposition in less than 50 years group. Commonest pathogen isolated in urine culture was E. coli (52.98%) followed by Klebsiella (39.09%), Citrobacter (8.76%), Pseudomonas (8.37%), Enterobacter (2.39%), Enterococci (1.99%), Candida (1.59%), Acinetobacter (1.2%), Proteus (1.2%), Streptococci (1.2%) and Serratia (0.4%).